Clinico-Radiological Features of Tumor-like Lesions of the Upper Limbs: don’t worry about those lumps - Ponti, Federico; Borlandelli, Elena; De Cinque, Antonio; Sambri, Andrea; De Paolis, Massimiliano; Rotini, Roberto; Marinelli, Alessandro (Current Medical Imaging, 2021)
Tumor-like lesions of the upper limb are more frequent than malignant neoplastic lesions and they represent a wide and heterogeneous group of disorders. The combination of clinical evaluation and imaging is the first pivotal step to attempt a distinction between benign and malignant masses, since there are important implications for further management, such as the requirement for conservative or interventional treatment. The classification of these pseudo tumoral lumps remains arbitrary and is still a matter of debate, currently based on a conjunct clinico-radiologic approach. In this article, we review various types of tumor-like lesions of the upper limb in terms of imaging approach and related clinic features, proponing a descriptive classification, useful in clinical practice to recognize these disorders, and to avoid unnecessary or potentially harmful procedures.
Keywords: Upper extremity